Uji Toksisitas Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Ulat Grayak (Spodoptera frugiperda) - Nofripa Herlina; Tria Pratikasari; Novia Gesriantuti (LPPM Universitas Muhammadiyah Riau, 2023)
Belimbing wuluh is a tropical tree that grows as a wild tree or planted because it contains many benefits. Belimbing wuluh is useful as traditional medicine and has secondary metabolite compounds such as tannins, flavonoids and saponins that function as insecticides. This study aims to determine the potential of Belimbng wuluh leaf extract as a natural insecticide against Fall armyworm (S. frugiperda) and to determine the concentration that can kill 50% of Fall armyworms (LC50). The method used for this research is a completely randomized design (CRD), Belimbing wuluh leaf extract made by maceration method. The concentration of the extract used was 0%, 60%, 80%, and 100%. The test larvae used were 40 tails. The parameters observed were mortality and speed of death. The result of this study showed that the number of Fall armyworm deaths was 66 from the total number of 120 larvae. This proves that Belimbing wuluh leaf extract has the potential as a natural insecticide against Fall armyworm (S. frugiperda). Based on probit analysis the effective concentration to kill 50% of Fall armyworm larvae was 59,9%. Key words :Belimbing wuluh (Averrhoa bilimbi L.), LC50, Mortality, Fall armyworm (Spodoptera frugiperda)